Pengaruh Kualitas Jasa, Kemudahan Transaksi, Dan Promosi Terhadap Loyalitas Konsumen Pt Xyz: Kepuasan Konsumen Sebagai Variabel Mediasi - Laura Debora (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine the main factors that can affect consumer loyalty PT XYZ. Based on previous research, three independent variables were obtained, namely: service quality, ease of transaction, and promotion. With variables mediating customer satisfaction. Loyalty is seen as one of the important criteria for companies to gain competitive advantage. The type of research conducted is descriptive research using a questionnaire distributed to 150 respondents in Jakarta. Data retrieval is done by non probability sampling method. Data analysis using regression analysis with SPSS. The results of the research findings prove that previous studies that the three independent variables taken significantly influence customer satisfaction in shaping consumer loyalty, service quality and promotion variables through mediation of customer satisfaction have a significant effect.